Increases in the source to sink ratio related to a higher carbohydrate concentration reduce phoma black stem in sunflower - Nuñez Bordoy, Evangelina; Quiroz, Facundo Jose; Dosio, Guillermo (Springer Netherlands, 2019)
Phoma black stem (BS), caused by Leptosphaeria lindquistii (synonymous Phoma macdonaldii Boerema) is an endemic disease of sunflower in Argentina and occurs worldwide. The expression of some diseases is related to the translocation of photosynthates during grain fill, which in turn is related to the source to sink ratio (SSr). The aim of this study was to assess the effect of total soluble carbohydrates (TSC) in the stem, and determine the effect of changes in SSr during the grain filling period on the incidence and severity of BS. A range of SSr and TSC was obtained by artificial shading and performing grain excision treatments, in two sunflower hybrids. A positive relationship was determined between SSr and TSC. Both the incidence and severity index of BS decreased with increasing SSr and TSC. This response was affected by the conditions of the experiment and the leaf position, for both incidence and severity of BS, respectively. Rainy days and leaf position (leaf age) were the main factors affecting the relationship between BS and TSC. Results contribute to understanding the physiological basis of the interaction between L. lindquistii and sunflower, and suggest how breeding for particular traits might result in improved cultivars. The results should also be useful for guiding management of the disease.